(I)mobilidades na Pré-história. Pessoas, recursos, objetos, sítios e territórios - Raquel Vilaça (Documentos, 2020)
(I) Mobilities in Prehistory. People, resources, objects, sites and territories is the result of the acknowledgement of human mobility as a central subject in archaeological research. It presents itself as a book with a plural and broad range, showcasing several contributions with distinctive theoretical and methodological approaches, multiple empirical case studies and different geographies across a large time span. This holistic and integrated framework is the one that is required to analyse mobility, a complex and multidimensional phenomenon of undeniable importance for the understanding of the dynamics that shaped past communities and their relations, not only between themselves, but also with the territory - dynamics that take shape in artefacts and structures, in built and lived landscapes bestowed to the passage of time. More than a contribution about a subject that explores divergent paths, this book intends, as well, to challenge other investigators to push forward a theme full of potential and relevance in a world that is now, more than ever before, in motion.